Investigating the role of tumor cell heterogeneity and angiogenesis genes in the prognosis of multiple myeloma - Qiao, Xue; Song, Zhengrong; Geng, Li; Xing, Lina; Wang, Ying (Frontiers in Immunology, 2025)
BackgroundMultiple myeloma (MM) is a common hematologic malignancy characterized by high tumor cell heterogeneity, which significantly impacts the clinical prognosis of patients. Angiogenesis and the molecular features of tumor cells play a critical role in tumor progression and drug resistance. This study aims to explore the impact of tumor cell heterogeneity and angiogenesis-related genes on the prognosis of MM.MethodsWe collected transcriptomic data and single-cell RNA sequencing data from MM patients through the Xena and GEO databases. The data were processed and analyzed using bioinformatics methods, including differential gene expression analysis, single-cell clustering, CNV analysis, transcription factor analysis, screening of angiogenesis-related genes, cell communication analysis, and immune infiltration analysis.ResultsThrough integrative analysis of transcriptomic data and single-cell RNA sequencing data, we identified significant genomic copy number variations in the tumor cells of MM patients. Additionally, different tumor subgroups exhibited differences in angiogenic activity, gene expression, and tumor progression. Notably, high expression of the transcription factor cAMP-responsive element-binding protein 3-like 2 (CREB3L2) in the C1 subgroup was associated with the inhibition of angiogenesis and tumor cell proliferation and migration. Furthermore, the prognostic model based on angiogenesis and transcription factors demonstrated high accuracy in predicting the prognosis of MM patients.ConclusionThis study highlights the critical roles of tumor cell heterogeneity and angiogenesis-related genes in MM. By constructing a prognostic model, it provides new theoretical insights for the precise diagnosis and personalized treatment of MM.